ANALISIS MANAJEMEN RESIKO OPERASIONAL PADA UMKM RUMAH MAKAN “BASABAH” MEDAN SEI MENCIRIM - Mayziyah Ayrin; Gizza Adinda Adellia Putri; Murima Febrianti; Natirian Zebua; Ayunda Fatmasari (Journal of Innovative and Creativity (Joecy), 2026)
PURPOSE - This study aims to identify, analyze, and design operational risk management strategies for the MSME "RM. Basaba," located on Jl. Johar Sei Mencirim, Sunggal District, Deli Serdang Regency, North Sumatra. The study seeks to ensure the efficient maintenance of the restaurant's operational continuity. METHOD - The research employs a qualitative descriptive approach, utilizing field observations and in-depth interviews with the business owner. The analytical framework is based on the four pillars of operational risk: Human Resources (HR), Internal Processes, Systems and Technology, and External Events. Risk mapping was conducted using a risk register table and a risk matrix (Heat Map) based on probability and impact level parameters FINDINGS - Identification results indicate that the risk with the highest severity level (an "extreme" score of 20/25) is a power outage, which directly halts the entire production process due to the reliance on electrically powered equipment. Subsequent risks include disruptions to the QRIS digital payment system (a "high" score of 12/25), which impede transaction flows, and the risk of fire (a "medium" score of 10/25), which has the potential to cause massive asset losses. Risk assessment was conducted using a likelihood-impact matrix (on a scale of 1–5) to generate a structured risk register. Furthermore, the implementation of structured Standard Operating Procedures (SOPs) proved crucial in minimizing losses. This study underscores that the implementation of systematic and structured operational risk management is a fundamental prerequisite for the sustainability and competitiveness of MSMEs amidst an uncertain business environment.